2010
DOI: 10.1590/s1516-35982010000900024
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the optimal level of concentrates for dairy cows on tropical pastures by using the concept of marginal analysis

Abstract: -It was adopted in this work a methodology to estimate the optimal level of concentrate food for dairy cows on tropical pastures based on the theory of marginal analysis. An empiric model was developed and validated for application of the methodology using a database composed of 62 means of treatments from 32 studies in which milk production was evaluated regarded to the levels of concentrate feeding. Milk production (MP) showed quadratic behavior in response to concentrate intake (CI): MP (kg/cow/day) = 10.55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
(21 reference statements)
0
4
0
9
Order By: Relevance
“…Although without differences between supplements, there was a higher milk production and milk corrected to 3.5% fat for the supplemented animals compared to those receiving only the mineral mix (Table 6). McLachlan et al (1994), Gibb et al (2002) and Oliveira et al (2010) demonstrated the importance of providing concentrate for dairy cows kept on pasture and its relationship to the increase in milk production. So, it is noteworthy that the exclusive use of forage does not allow the enhancement of milk production, even in cows of low average production in the final third of lactation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although without differences between supplements, there was a higher milk production and milk corrected to 3.5% fat for the supplemented animals compared to those receiving only the mineral mix (Table 6). McLachlan et al (1994), Gibb et al (2002) and Oliveira et al (2010) demonstrated the importance of providing concentrate for dairy cows kept on pasture and its relationship to the increase in milk production. So, it is noteworthy that the exclusive use of forage does not allow the enhancement of milk production, even in cows of low average production in the final third of lactation.…”
Section: Resultsmentioning
confidence: 99%
“…Using the equation proposed by Oliveira et al (2010) obtained by analysis of 31 experiments, a calculated marginally productive response of 1.38 kg of milk per kg of concentrate was obtained. The discrepancy between the marginal productive responses observed and calculated shows the low productive potential of the cows in late lactation is associated with the reduced nutritional value of forage during the experiment and justified, in part, the absence of differences between supplements.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al (2010) encontraram, ao utilizar o conceito de análise marginal para estimar o nível ótimo de suplementação com alimentos concentrados para vacas de leite em pastagens utilizando dados de 31 trabalhos sobre a avaliação da produção de leite de vacas em sistemas de pastos tropicais, produção média de 10,5 kg vaca -1 dia -1 em dietas exclusivas com pastos tropicais e resposta curvilínea (P < 0,05) da produção de leite em função do consumo de suplemento, estando os dados de acordo com o presente trabalho.…”
Section: Resultsunclassified
“…No início do século passado, Mitscherlich (1909) propôs a teoria da resposta marginal (ou rendimentos) decrescente do fornecimento de nutrientes cujos princípios foram essenciais para definição do nível ótimo de suplementação concentrada utilizados na atualidade (Lana et al, 2005;Lana, 2009;Oliveira et al, 2010;Oliveira et al, 2012) mas, de acordo com o Biotechnology andBiological Sciences Research Council (1998), os sistemas alimentares em uso calculam os requerimentos dietéticos de energia e proteína que os animais requerem para satisfazer suas necessidades para manutenção visando a um dado nível de produção; todavia, na prática a situação é diferente, porque não existe qualquer necessidade do produtor satisfazer os requerimentos nutricionais das vacas se for contra os interesses econômicos. Evidencia-se, desta forma, a necessidade de estudos de resposta animal aos níveis crescentes de suplementos.…”
Section: Introductionunclassified
See 1 more Smart Citation